Arab Muslims in TV Screens: The Reproduction of Reality by the American Entertainment Industry in the Age of Contemporary Radical Armed Groups - Benziane, Mohammed Nabil; Abdelhay, Bakhta (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست, 2020)
مثلت شخصية العربي المسلم دائما قضية إشكالية في منتجات هيئة صناعة الترفيه الأمريكية بدءا من العنف والتخلف مرورا بالتعصب والغرائبية، ووصولا إلى الإرهاب، بنية تشويه صورة العرب المسلم بطريقة أيديولوجية لتعزز كل هذه الافتراضات المجسدة فعليا. مثل هكذا تصوير، كما هو الاهتمام الفعلي لهذا المقال، الذي يهدف إلى إعادة إنتاج "الواقع المتواجد فعلا" من وجهة نظر متحيزة، والتي تهدف بدورها إلى الترويج لصورة "العربي الشرير". في سبيل دراسة الصورة المشوهة للعرب المسلمين يتجلى التحليل السيميائي منهجا مهما لتفكيك الغطاء ونزعه عن هذا الخطاب الأيديولوجي المتجذر في المنتجات السينمائية، وأيضا لفحص الكيفية التي تمت بها عملية إنتاج الواقع لكي تمثل "وعيا اجتماعيا" للعرب والمسلمين. مع ذلك، أسهمت الجماعات المتطرفة المعاصرة بشكل كبير في ترسيخ صورة "المسلم المتعصب" على شاشات التلفاز بإظهارها علنا ولائها لبعض الأيديولوجيات المتطرفة وبالتالي مثلوا صورة خاطئة عن الإسلام والمسلمين مما أدى في الأخير بهيئة صناعة الترفيه الأمريكية إلى اعتبار صورتهم كحقيقة مجسدة فعليا عن العرب المسلمين.
The Arab Muslim character has always represented a problematic issue in the outputs of the American Entertainment Industry. From violence and backwardness, through fanaticism and exoticism to recently terrorism, the image of Arab Muslims has been ideologically structured to reinforce these already settled presumptions. This representation, as the paper at hand is concerned, attempts to reproduce "reality out there" from a biased perspective that aims, in turn, to promote the image of "villain Arabs". In the process of examining this vilified depiction of Arab Muslims, semiotic analysis stands out to be one prominent approach to decipher and reveal the unsaid about this ideological discourse which is inherent in cinematic products and, yet, to inspect the way in which reality is reproduced so that to manifest as "social consciousness" about Arabs and Muslims. The contemporary radical armed groups, however, extensively contributed to uphold the image of "fanatic Muslims" in TV screens as they show adherence to certain extremist ideologies, therefore, they present an erroneous image of Islam and Muslims. Ultimately, this picture is considered by the American Entertainment Industry as "reality out there" about Arab Muslims.
Keywords: الجرائم الإرهابية -- التعصب الديني -- المنتجات السينمائية -- الترفيه الإمريكي -- الوطن العربي